PELAKSANAAN ASIMILASI DI RUTAN KELAS IIA SAMARINDA SEBAGAI REALISASI DARI SISTEM PEMASYARAKATAN - Dedy Tri Widodo (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACT Inmates in the legal status of a person guilty (evil) for the actions he did. Past mistakes do not make people prisoners about stamps (stigma) nasty to him. Therefore they should not lose contact with the people that feel the same as people and not experience keminderan in the mix pidananya.hal later after a period of what is called the assimilation or integration of prisoners into society. Based on the purpose of sentencing that this is a case of the state through legislation seeks to accommodate the integration efforts of inmates into the community environment. Some rules are considered to be very influential in the assimilation of prisoners is Law No. 12 Year 1995 on Penal and Government Regulation No. 31 Year 1999 About Coaching and Mentoring correctional inmates. Based on the above reasons, then the problem can be formulated as follows: first, how the implementation of coaching prisoners in the assimilation stage at the Detention Class II A Samarinda? second, whether the constraints in the implementation of the assimilation of inmates at the Detention Class II A Samarinda and efforts to overcome it? third, whether it is effective or not the implementation of Assimilation in State Prison Class II A Samarinda?From the research and discussion of some conclusions are obtained: the first implementation of assimilation at the Detention Class II A form of assimilation Samarinda generally work with a third party, the second, the many obstacles encountered, thus hampering the smooth assimilation programs and the efforts made by the parties Detention Class II A Samarinda in pelancaran assimilation program is quite good although unfettered flexibility in its implementation on the existing legal framework, only the results of these efforts are still not visible factually. Third, the implementation of Assimilation in the Detention Class II A has been effective Samarinda, where a PLT after diteima can freely fully in society.